Comparison of Survival in Patients with Isolated Peritoneal Carcinomatosis from Colorectal Cancer Treated with Cytoreduction and Melphalan or Mitomycin-C as Hyperthermic Intraperitoneal Chemotherapy Agent. (13th December 2018) - Sipok, Arkadii; Sardi, Armando; Nieroda, Carol; King, Mary Caitlin; Sittig, Michelle; Gushchin, Vadim
Abstract : Background . The role of hyperthermic intraperitoneal chemotherapy (HIPEC) for peritoneal carcinomatosis (PC) from colorectal cancer (CRC) is debated. Melphalan as a perfusion agent has also demonstrated survival benefit in other recurrent and chemoresistant malignancies. Thus, we hypothesize that melphalan as a HIPEC agent may improve overall survival (OS) and progression-free survival (PFS) in patients with PC from CRC. Methods . A retrospective review of a prospective database of 48 patients who underwent optimal CRS (CC-0/1) and HIPEC from 2001-2016 was performed. Nineteen had CRS/HIPEC with melphalan (group I) and 29 with mitomycin-C (group II). Survival was estimated using the Kaplan-Meier method. Cox regression was used for multivariate analysis. Perioperative variables were compared. Results . Mean age at CRS/HIPEC was 53±10 years. Median peritoneal cancer index (PCI) was 17 vs 13 in groups I and II, respectively (p=0.86). PCI≥20 occurred in 9 (47%) and 13 (45%) patients in groups I and II, respectively. Positive lymph nodes were identified in 8/19 (42%) vs 12/29 (41%) in groups I and II, respectively (p=0.73). Multivariate analysis identified PCI≥20 as a predictive factor of survival (HR: 7.5). Median OS in groups I and II was 36 and 28 months, respectively (p=0.54). Median PFS in groups I and II was 10 and 20 months, respectively (p=0.05). Conclusions . CRS/HIPEC with MMC had longer median PFS in PC from CRC. PCI≥20 was the only independent predictive factor for survival. Until longer follow-up is available, we recommend using MMC in CRS/HIPEC for PC from CRC. Further prospective randomized studies are necessary.